2021
DOI: 10.3390/ma14195672
|View full text |Cite
|
Sign up to set email alerts
|

Study on Ultraviolet Aging Mechanism of Carbon Nanotubes/SBS Composite-Modified Asphalt in Two-Dimensional Infrared Correlation Spectroscopy

Abstract: In order to explore the influence mechanism of carbon nanotubes on the ultraviolet (UV) aging properties of the SBS-modified asphalt binder, the changes of functional groups in the one-dimensional infrared spectrum and two-dimensional infrared correlation spectrum are studied in this paper. The results show that the UV aging process of the SBS-modified asphalt binder is the process of alkane chain cleavage and reorganization, the formation of oxygen-containing functional groups and decomposition of SBS. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…A C C stretching vibration peak appearing at 1650 cm −1 of the CNTs@CA fibrous membrane could be attributed to sp 2 hybridization of the carbon–carbon double bonds in CNTs. 45 These phenomena indicated that CNTs were well doped.…”
Section: Resultsmentioning
confidence: 98%
“…A C C stretching vibration peak appearing at 1650 cm −1 of the CNTs@CA fibrous membrane could be attributed to sp 2 hybridization of the carbon–carbon double bonds in CNTs. 45 These phenomena indicated that CNTs were well doped.…”
Section: Resultsmentioning
confidence: 98%
“…In order to verify the reliability of the asphalt binder model, Table 3 presents the simulated and experimental data of the (i) density, (ii) glassy transition temperature, (iii) solubility parameters and (iv) diffusion coefficient. As an important index in molecular simulation, the density of the asphalt binder model at 298.15 K is 0.981 (g/cm 3 ), which is lower than the density of 1.01-1.04 (g/cm 3 ) obtained in the experiment, which may be due to the excessive complexity of the asphalt binder components, and the asphalt binder model constructed with 12 representative molecules cannot fully represent the complex composition of the actual asphalt materials.…”
Section: Model Verificationmentioning
confidence: 90%
“…After establishing 12 representative molecules of AAA-1 asphalt binder, the combined model of AAA-1 asphalt binder was established by Packmol; the initial model size was 140 Å × 140 Å × 140 Å, and the density was approximately equal to 0.1 g/cm 3 . The simulation steps used in this paper are shown in Table 2.…”
Section: Details Of the Molecular Dynamics Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of IR spectroscopy to monitor non-thermal decomposition and chemical alterations of materials involve the study of UV aging of asphalt involving carbon nanotubes/polystyrene composite, 370 as well as alterations of microplastics, 371 discharge-initiated decomposition of SF6, 372 and environmental degradation of various real-world materials. 373,374 The experiments in transmission mode usually require the use of alkaline halogenide matrix materials, most commonly KBr.…”
Section: Other Chemical Processesmentioning
confidence: 99%